Media, policy and interaction - Fitzgerald, Richard; Housley, William, 1970- (Ashgate Pub., 2009)
Situated within the field of discourse-oriented approaches to policy and media, this collection explores the interface between government, media and the public, highlighting the increasing importance placed on media channelled 'public opinion' as part of a democratic process. It will appeal to a broad audience in social and public policy, political communication, journalism and politics.